Research handbook on intellectual property in media and entertainment - Richardson, Megan; Ricketson, Sam (Research handbooks in intellectual property, 2017)
The phenomenal growth of the media and entertainment industries has contributed to a fragmented approach to intellectual property rights. Written by a range of experts in the field, this Handbook deals with contemporary aspects of intellectual property law (IP), and examines how they relate to different facets of media and entertainment. A stimulating array of chapters cover topics such as: IP rights in the news, spectacles and other ephemera; copyright and fan activities; performers' and moral rights; IP protection of television formats; publicity and personality rights; trade marks in entertainment products; traditional knowledge, and the global digital distribution of media content. Highlighting the need for the law to accommodate a rapidly expanding and modernizing industry, suggestions are made for future developments. Novel and contemporary, this Handbook will appeal to both academics and students across the field of IP, particularly in relation to media and entertainment. Its practical focus will also appeal to both practitioners and judges looking to work within and develop this most fascinating and topical area of the law.